1993
DOI: 10.1080/00039896.1993.9938387
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Illness from Chemical Odors in Young Adults without Clinical Syndromes or Occupational Exposures

Abstract: The present survey of young adult college students investigated the prevalence of self-reported illness from the smell of the five following common environmental chemicals (cacosmia): (1) pesticide, (2) automobile exhaust, (3) paint, (4) new carpet, and (5) perfume. Sixty-six percent of 643 students reported feeling ill from one or more of the five chemicals; 15% identified the smell of at least four chemicals as making them ill. Ratings of illness from pesticide correlated weakly but significantly with rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
2
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(69 citation statements)
references
References 40 publications
2
63
2
2
Order By: Relevance
“…Two subsequent studies also used subjects from specialized subgroups: one sample group was composed of 809 young adult college students (Bell et al 1993) and one group comprised 160 elderly persons (Bell et al 1997), both in Arizona. In these studies (Bell et al 1993(Bell et al , 1997, approximately 15% of the younger sample and more than 37% of the elderly group reported a hypersensitivity.…”
Section: Mcs Prevalencementioning
confidence: 99%
“…Two subsequent studies also used subjects from specialized subgroups: one sample group was composed of 809 young adult college students (Bell et al 1993) and one group comprised 160 elderly persons (Bell et al 1997), both in Arizona. In these studies (Bell et al 1993(Bell et al , 1997, approximately 15% of the younger sample and more than 37% of the elderly group reported a hypersensitivity.…”
Section: Mcs Prevalencementioning
confidence: 99%
“…Bell et al (14) found that 66% of college students reported illness from at least one of five listed chemicals (pesticides, auto exhaust, paint, new carpets, and perfume), and 15% from at least four of the chemicals, and also up to 30% of the general population report milder forms of chemical intolerance, without disability (83). Meggs et al (11) found, in a random household sample of 1,027 people polled in North Carolina, that 33% reported chemical sensitivity, with the major incitants being perfume, pesticides, cigarette smoke, and fresh paint.…”
Section: General Populationmentioning
confidence: 99%
“…With regard to gender difference, Bell et al (14) stated that females outnumber males as environmental illness patients by a ratio of 2 : 1. Clinical samples studied by some authors (98)(99)(100)(101)(102) were also predominantly women.…”
Section: Gendermentioning
confidence: 99%
See 2 more Smart Citations